When is it Optimal to Exhaust a Resource in a Finite Time? - Y. Hossein Farzin; Ken-Ichi Akao (Fondazione Eni Enrico Mattei (FEEM), 2006)
Exhaustion of a natural resource stock may be a rational choice for an individual and/or a community, even if a sustainable use for the resource is feasible and the resource users are farsighted and well informed on the ecosystem. We identify conditions under which it is optimal not to sustain resource use. These conditions concern the discounting of future benefits, instability of social system or ecosystem, nonconvexity of natural growth function, socio-psychological value of employment, and strategic interaction among resource users. The identification of these conditions can help design policies to prevent unsustainable patterns of resource use.
Keywords: Q20; 330; Renewable resource management; Sustainability; Finite-time exhaustion; Optimal path; Policy implications; Erneuerbare Ressourcen; Nachhaltige Entwicklung; Theorie